2000
DOI: 10.1159/000063442
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bone Architecture with Ultrasonometry: Experimental and Clinical Experience

Abstract: Over the last decade, ultrasound technology has been introduced as a method of analysing bone tissue in clinical practice, and several studies have compared various ultrasound devices with dual-energy X-ray absorptiometry (DXA). Unlike DXA, the ultrasound technique is not limited to the measurement of bone density – it also has the potential to provide information on the mechanical and architectural characteristics of bone. The first generation of ultrasound devices used the speed of sound and attenuation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A study involving obese patients found a lower lumbar spine BMD than was expected for age and BMI (21). In several studies carried out by using QUS, soft tissues were proved to reduce the speed of sound (SOS) transmitted across bones (22); on the basis of these studies, some authors have proposed that the negative impact of BMI on QUS parameters can be ascribed to the interference of soft tissues (23). In their paper, Biino et al, found a negative correlation between AD-SoS and BMI, with AD-SoS showing the highest correlation coefficient with BMI among all among QUS parameters (23).…”
Section: Discussionmentioning
confidence: 99%
“…A study involving obese patients found a lower lumbar spine BMD than was expected for age and BMI (21). In several studies carried out by using QUS, soft tissues were proved to reduce the speed of sound (SOS) transmitted across bones (22); on the basis of these studies, some authors have proposed that the negative impact of BMI on QUS parameters can be ascribed to the interference of soft tissues (23). In their paper, Biino et al, found a negative correlation between AD-SoS and BMI, with AD-SoS showing the highest correlation coefficient with BMI among all among QUS parameters (23).…”
Section: Discussionmentioning
confidence: 99%
“…and mass are correlated with body size, physical activity and muscle strength [1,2]. Delayed puberty, growth hormone deficiency, hypothyroidism and other diseases can result in lower bone mass and size.…”
Section: Introductionmentioning
confidence: 99%